Developing agricultural markets in sub-Saharan Africa: organic cocoa in rural Uganda - (:unkn) unknown (My University, 2011)
This paper investigates the process of development in a traditional African export market, focussing on a contract farming scheme for organic cocoa in rural Uganda. Based on a repeated household survey, we measure the impact of the scheme on the income of participants and the economic mechanisms behind these effects. We find substantial benefits from the scheme, driven primarily by the establishment of credible incentives for farmers to adopt technologies which improve cocoa quality. There is also evidence of broader trends of market deepening and increased productivity, likely due to positive spillovers.
Keywords: African Research